Memberdayakan Masyarakat melalui Penerapan Proses Filtrasi Air Tanah untuk Meningkatkan Akses Air Bersih Keluarga Balita Stunting - Supardi, Ardiani; Ardiani Septiati, Yosephina; Karmini, Mimin; Karjatin, Atin (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: Low access to clean water can be an indirect cause of stunting in toddlers, because water needs for cleanliness and sanitation at home are not met, making toddlers easily susceptible to diseases such as diarrhea. RW 16 and RW 14 The working area of ​​the Dayeuhkolot Health Center, Bandung Regency is an industrial area, densely populated, a flood area and there are cases of stunting. People use groundwater as a source of clean water with iron and manganese levels that do not meet the requirements. The activity aims to increase knowledge, improve water processing skills for the community and provide access to clean water for families of stunted toddlers. Method: This community service uses lecture methods, questions and answers, air filter maintenance training interventions and groundwater treatment interventions, with a target of 20 peoples in each RW. The activity begins with a pre-test measuring knowledge, skills, checking iron and manganese levels in groundwater before air processing followed by providing counseling, intervention in making air filters, training in using and caring for filters and filter media. The post test uses the same pre-test questionnaire for knowledge, skills checklist and examination of laboratory parameters. The results: shown increase knowledge by 40%, improve skills. Water treatment interventions reduce the iron and manganese levels of clean water until they meet the requirements and families of stunted toddlers can access clean water. Conclusion: This activity increases community knowledge and skills in providing clean water and increases clean water for families of Stunting Toddlers.